Konflik Politik Internal Kerajaan: Prolog Islamisasi Massif dan Struktural di Bima - Nurhilaliati Nurhilaliati (Ulumuna, 2005)
Bima used to be well known as a producer of high quality spices, and attracted many traders from Sumatera, Sulawesi, and Java which then led Bimanese traders and people in general into a direct communication and interrelationship among traders from other places outside Bima. It in turn resulted in broader contact among different cultures, traditions, and religions. This was the starting point that Bimanese people began to be influenced by the new religion, Islam, which then attracted them to be its followers, Muslims. The process of coming and spreading of Islam in Bima ran through phases from an early contact with Muslim traders from outside Bima to a structural and massive islamization by the power of Bima Sultanate. Many factors played their respective roles in supporting or obscuring the process. But, above all other factors, political conflict among the ruling royals in Bima Kingdom was the most significant one. It was the conflict between Tureli Nggampo (Prime Minister) Salisi and Jena Teke (crown prince), which then resulted in assassination on the later. Salisi declared himself the King of Bima. Next Jena Teke (younger brother of the killed first Jena Teke) with the help of Gowa Sultanate took over Salisi’s crown. This political conflict can be considered a blessing in disguise in terms of it was the turning point and gateway of structural and massive islamization in Bima.